(untitled) (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
This study aims to analyze the influence of Leadership Style, Organizational Culture, Work Motivation, and Work–Life Balance on the Performance of the Brimob Corps Members of Paniki Dua in Manado City, North Sulawesi. The background of this research stems from the need to understand the dynamics of police officers’ performance, which is shaped by various internal and external organizational factors. The performance of police personnel—especially Brimob members who face high-risk duties—depends greatly on the leadership patterns applied within the unit, the strength of the organizational culture, the level of work motivation, and the members’ ability to balance demanding job responsibilities with their personal lives. Therefore, this study is crucial for providing empirical insights into the key factors that determine performance improvement in the field. The research employed a quantitative approach using survey techniques, with questionnaires distributed to 100 Brimob members as the research sample. The collected data were then analyzed using the Statistical Product and Service Solutions (SPSS) software to examine statistical relationships and effects among the variables. This approach was chosen to ensure objective, measurable, and scientifically accountable results. The findings show that Leadership Style has a significant but negative influence on member performance. This indicates that the leadership approach currently applied has not fully succeeded in enhancing performance and may even create pressure or discomfort among members. In contrast, Organizational Culture is found to have a significant and positive effect on performance, demonstrating that a conducive work environment, strong organizational values, and well- structured work systems can effectively enhance members’ productivity. Keywords: Leadership Style, Organizational Culture, Work Motivation, Work-Life Balance, Performance, SPSS – IBM SPSS software